2011
DOI: 10.1111/j.1741-2358.2011.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Resonance frequency analysis of overdenture retainer implants with immediate loading

Abstract: Resonance frequency analysis of overdenture retainer implants with immediate loadingObjective: To evaluate 16 patients of both sexes with lower overdenture and upper complete dentures, by analysing the resonance frequency of the initial and late stability of implants used to retain the overdenture under immediate loading. Background: Oral rehabilitation treatment with complete dentures using implants has been increasingly more common among the specialists in the oral rehabilitation area. This is an alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In addition, the immediate loading of non-splinted implants might increase micro-movements and marginal bone loss affecting implant stability. These results were in agreement with other studies of immediate loading for lower overdentures [42,43].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the immediate loading of non-splinted implants might increase micro-movements and marginal bone loss affecting implant stability. These results were in agreement with other studies of immediate loading for lower overdentures [42,43].…”
Section: Discussionsupporting
confidence: 93%
“…Our ISQ results are similar to those of Elsyad et al, 49 who observed a significant decrease in ISQ in the IML group compared to the CL group in a patient sample of IMO wearers 6 months after implant installation, whereas differences between groups were not observed at 12 months 49 . Silva et al also observed that the ISQ of implants submitted to IML as IMO retainers was smaller at 3 months compared to baseline, however, the mean ISQ values increased to six points above the baseline values after 15 months 50 . The IML‐specific bone remodeling process can thus delay the secondary stability of the implant, yet bone tends to stabilize through formation of dense bone or trabecular bone after mineralization, resulting in a situation comparable to CL 12 months after implant installation 14,49‐51 …”
Section: Discussionmentioning
confidence: 96%
“…50 The IML-specific bone remodeling process can thus delay the secondary stability of the implant, yet bone tends to stabilize through formation of dense bone or trabecular bone after mineralization, resulting in a situation comparable to CL 12 months after implant installation. 14,[49][50][51] The delay in the secondary stability that was observed in the IML group can also be linked to the cytokine release patterns. The IML protocol is known to promote an accelerated, more intense release of bone mediators around the implants already in the first days after implant installation, 22,23 and this can be maintained until 6 months after loading.…”
Section: Clinical and Biological Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…De Smet et al 10 did not find statistically significant differences in individual implants stability when using the Novum protocol after 2 years in function, but there were 5 implants lost from 30 that were inserted according to the Novum protocol. In a 15-month follow-up study, da Silva et al, 3 using overdentures, observed statistically significant increase in stability after 15 months of implants in function (right sidedbaseline mean 72.13, 15 months mean 78.9 ISQ; and left sidedbaseline mean 71.54, 15 months mean 76.64 ISQ).…”
Section: Discussionmentioning
confidence: 93%